Prevalence of stunting and associated factors among neonates in Shebadino woreda, Sidama region South Ethiopia; a community-based cross-sectional study 2022 - Gizu Tola; Andargachew Kassa; Melkamu Getu; Bekem Dibaba; Shambel Neggesse (BMC, 2023)
Abstract Introduction Stunting is a syndrome that begins at conception and leads to severe, irreversible physiological, physical and cognitive damage as an irreversible consequence of nutritional deficiencies and recurrent infections. Although multiple studies have been conducted in Ethiopia to show the magnitude of stunting and factors, all are concentrated on children aged between 6 to 59 months. Therefore, this study was done to determine the prevalence and associated factors of stunting at birth among new-borns. Methods A community-based cross-sectional study design was employed on 512 neonates in Shebadino Woreda, Sidama Region South Ethiopia 2022. A multistage sampling technique was employed. The data was collected door-to-door using pretested and structured questionnaires, through face-to-face interviews. The collected data were cleaned manually, coded, entered into Epidata version 4.6, and exported to SPSS version 26 software for analysis. Bi-variable analysis was conducted to assess the association of independent variables with the outcome variable. Variables with a p-value < 0.25 in bi-variable logistic regression were further analyzed using multivariable logistic regression. The odds ratio (OR) with 95% CI was used as a measure of association, and variables that had a p-value less than 0.05 in the multivariable logistic regression were considered as significantly associated variables. Result The prevalence of stunting in this study was 27.5%: 95% CI 22.6 to 31.9. Factors such as residence (AOR = 4.1, 95% CI: 1.49, 11.25), ANC follow up (AOR = 2.66, 95% CI: 1.34, 5.27), started taking Amessa (AOR = 3.48, 95% CI: 1.27, 9.55) and Sex of the neonate (AOR = 2.15, 95% CI: 1.54, 5.23) were significantly associated with stunting at a p-value of < 0.05. Conclusion About 27% of neonates were stunted, which implies, it require a quick public health measurement. New-born who were live in rural area and those who were started traditional medication (Amessa) were more stunted. Besides this, stunting was prevalently observed among a mother who had no ANC follow-up and male neonates. Thus, the regional health bureau and Shebedino woreda health office should increase awareness creation to bring behavioural change at community level to prevent traditional medication usage, ANC follow-up and giving priority for those who live in rural area.